Ark angel - Horowitz, Anthony 1955- (New York Speak, 2007)
After recovering from a near fatal gunshot wound, teenage spy Alex Rider embarks on a new mission to stop a group of eco-terrorists from sabotaging the launch of the first outer space hotel.
Keywords: Spy stories; Adventure and adventurers -- Juvenile fiction; Orphans -- Juvenile fiction; Terrorism -- Juvenile fiction